(untitled) (Observatorio Económico, 2009)
Although there have been reports of people offering to buy or sell organs on eBay, the fact is that the idea is repugnant. No one wants to see the wealthiest buying their place on waiting lists, much less the poor cashing in on pieces of their own bodies. Continue reading...